Bioreducible poly(amido amine) copolymers derived from histamine and agmatine for highly efficient gene delivery. Issue 3 (27th November 2018) - Sun, Yanping; Liu, Hui; Xing, Haonan; Lang, Lang; Cheng, Lin; Yang, Tianzhi; Yang, Li; Ding, Pingtian
Abstract: Histamine (HIS) can facilitate the endosomal escape of polyplexes via the 'proton sponge effect' because of its imidazole groups. Agmatine (AGM) can improve the transmembrane process of polyplexes as a result of its guanidinium groups. Therefore, HIS and AGM were used as amino monomers to react with cystamine bisacrylamide (CBA) through Michael addition. The synthesized peptide‐mimicking poly(CBA‐HIS/AGM)s showed high transfection efficiency and low cytotoxicity, indicating their great potential as gene carriers. The results also demonstrated that the effects of HIS and AGM on the properties of poly(CBA‐HIS/AGM)s were different: HIS could increase their buffering capacities and bioreducibility, but AGM could facilitate their plasmid DNA packaging and condensing abilities. In addition, the results of transfection mechanism studies indicated that poly(CBA‐HIS/AGM) polyplexes entered into cells mainly via clathrin‐dependent endocytosis and they could efficiently escape the endosome, indicating endosomal escape was not the limiting step for gene delivery based on these polymers. © 2018 Society of Chemical Industry Abstract : A new type of bioreducible poly(amido amine) copolymer is synthesized. These smart polymers could efficiently condense plasmid DNA, successfully deliver it into cells, and finally facilitate gene expression.